2015
DOI: 10.1186/s12888-015-0532-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and change mechanisms of psychotherapy among depressed patients: study protocol for a multicenter randomized trial comparing twice-weekly versus once-weekly sessions of CBT and IPT

Abstract: BackgroundCognitive behavioral therapy (CBT) and interpersonal therapy (IPT) are among the most well established therapies for the treatment of depression. However, some major questions remain unanswered. First, it is unknown what session frequency results in the most optimal (cost) effectiveness in psychotherapy. Second, the debate as to what mechanisms underlie the effect of psychotherapy has not yet been resolved. Enhancing knowledge about the optimal session frequency and mechanisms of change seems crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 66 publications
1
40
0
1
Order By: Relevance
“…For a detailed description of these instruments and their psychometric properties, we refer to our protocol paper. 9…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…For a detailed description of these instruments and their psychometric properties, we refer to our protocol paper. 9…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…Our hypothesis is that a higher session frequency leads to better recall of the content of the sessions, which will lead to a better development of therapy-specific skills and consequently better treatment outcomes. 9 An alternative hypothesis is that a higher session frequency leads to a better working alliance, which then leads to better patient adherence and motivation, and consequently better treatment outcomes. This is the first randomised trial to investigate the effects of once weekly versus twice weekly sessions of CBT and IPT for depression.…”
mentioning
confidence: 99%
“…These interpersonal problems that may be due to negative cognitive deviation, anhedonia, and emotional regulation deficits have important roles in the onset and maintenance of the depressive state. In addition, many effective short-term treatment strategies target the improvement of interpersonal problems, such as interpersonal psychotherapy (IPT) (Bruijniks et al, 2015 ). However, the neuropsychological mechanisms of this impaired interpersonal function in depression are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported herein is a pragmatic pilot trial that has been conducted as part of a series of Dutch trials in outpatient settings. Despite the original CT manual (Beck, Rush, Shaw, and Emery 1979) recommending two weekly sessions in the beginning of therapy, most therapists in Europe generally see their patients only once per week (Bruijniks et al 2015). Therefore, the first aim of this trial was to test the implementation of a regimen of two psychotherapy sessions per week.…”
mentioning
confidence: 99%
“…Therefore, the first aim of this trial was to test the implementation of a regimen of two psychotherapy sessions per week. Secondly, we wanted to inform a large ongoing study described in Bruijniks et al (2015) on the effects of session frequency and other mechanism of change in psychotherapy for depression. Thirdly, we intended to provide a benchmark for the effectiveness and mechanism trial by Lemmens et al (2015), which compared one session per week of CT to interpersonal psychotherapy (IPT).…”
mentioning
confidence: 99%